2020
DOI: 10.3892/etm.2020.8534
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA np_5318 promotes renal ischemia‑reperfusion injury through the TGF‑β/Smad signaling pathway

Abstract: Long noncoding (Lnc)RNA np_5318 has been proved to be involved in renal injury, while its functionality in renal ischemia-reperfusion (I/R) injury is unknown. Therefore, the present study aimed to investigate the role of lncRNA np_5318 in the development of renal I/R injury. Renal I/R injury model and I/R cell model were established in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…AKI refers to is a common complication in hospitalized patients and renal I/R injury is implicated in the pathophysiology of AKI [ 41 , 42 ]. As reported previously, numerous lncRNAs are upregulated in renal I/R injury [ 17 , 43 , 44 ]. For example, the expression of lncRNA MALAT1 in rats with renal I/R injury is distinctly higher than that in the control group [ 43 ].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…AKI refers to is a common complication in hospitalized patients and renal I/R injury is implicated in the pathophysiology of AKI [ 41 , 42 ]. As reported previously, numerous lncRNAs are upregulated in renal I/R injury [ 17 , 43 , 44 ]. For example, the expression of lncRNA MALAT1 in rats with renal I/R injury is distinctly higher than that in the control group [ 43 ].…”
Section: Discussionmentioning
confidence: 67%
“…For example, the expression of lncRNA MALAT1 in rats with renal I/R injury is distinctly higher than that in the control group [ 43 ]. The expression of lncRNA np_5318 is strikingly elevated in I/R-induced cell models of renal injury [ 44 ]. The expression of lncRNA TUG1 is markedly upregulated in renal tissues of I/R-induced rats compared with control group [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have indicated that long noncoding RNAs (lncRNAs) are tightly related to IRI, such as lncRNA MALAT1 in myocardial IRI [ 13 ], lncRNA AK139328 in hepatic IRI [ 14 ], and lncRNA np_5318 in RI/RI [ 15 ]. It has been well documented that lncRNA X-inactive-specific transcript (XIST) takes part in the regulation of many kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] Accumulating studies have revealed the important regulatory roles of lncRNAs in renal IRI including TUG1. [43][44][45] TUG1 was recently reported to play important roles in ischaemia-induced oxidative damage including in kidney, cardiac or cerebrum. 14,46,47 MiR-144-3p was confirmed to be a target of TUG1 in tumour models, 18,19 however, among all these studies related to oxidative damage, miR-144-3p was never studied as a target of TUG1.…”
Section: Discussionmentioning
confidence: 99%